Longitudinal variation characteristics of stable isotope ratios of suspended particulate organic matter in the headwaters of the Qingjiang River, China - Gao Jian; Zehui Zhang; Zhong Ping; Cheng Yang; Liao Mingjun; Jiao Yiying (Knowledge and Management of Aquatic Ecosystems, 2021)
To determine the sources and characteristics of suspended particulate organic matter (SPOM), the spatial distribution of carbon and nitrogen and their isotopic values (δ13C and δ15N) were measured from upstreamto downstream (i.e. site 1 to site 4) in the head waters of the Qingjiang River in central China. The mean annual SPOM δ15N and δ13C values varied between sites but exhibited a unimodal pattern. The mean annual δ15N increased from site 1 (2.5‰) to 3 (5.3‰), followed by a major decrease to 2.2‰ at site 4. Furthermore, the mean annual δ13C varied unimodally, being the most positiveat sites 1 (−21.6‰) and 4 (−22.8‰) followed by sites 2 (−24.5‰) and 3 (−26.4‰). In particular, the mean SPOM δ15N and δ13C in the tailwaters from a domestic wastewater treatment plant, which was located approximately 0.3 km upstream of site 4, were 2.2‰ and −25.6‰, respectively. The SPOM C/N values from stream water at site 4 (8.5 ± 1.5) and tailwater (6.2 ± 0.9) were similar. Collectively, the results suggested that wastewater treatment plant tailwater influenced the stable isotope values of SPOM in the stream and affected the variation trendfrom upstream to downstream.